2008
DOI: 10.3892/mmr.1.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between peroxisome proliferator-activated receptor-γ and renal ischemia-reperfusion injury

Abstract: Abstract. The pathogenesis of ischemia-reperfusion (I/R) injury is known to involve cytokines and, in particular, surface adhesion molecules, the expression of which initiates inflammatory cell attachment. It has been suggested that peroxisome proliferator-activated receptor (PPAR)-γ is an important immunomodulatory factor as well as a regulator of fatty acid. In this study, we investigated the expression of PPAR-γ in a renal I/R injury rat model. The right kidney was harvested and the left renal artery and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…PPARγ expression in cyclosporine-treated rat kidneys was significantly lower than that in the control groups (34). Matsuyama et al (35) also showed that PPARγ expression was reduced in rats following ischemia/re-perfusion. The discrepancies between these previous studies and the results of the present study may be due to differences in treatment or stimulus intensity, or due to differences between experimental in vitro and in vivo models.…”
Section: Discussionmentioning
confidence: 95%
“…PPARγ expression in cyclosporine-treated rat kidneys was significantly lower than that in the control groups (34). Matsuyama et al (35) also showed that PPARγ expression was reduced in rats following ischemia/re-perfusion. The discrepancies between these previous studies and the results of the present study may be due to differences in treatment or stimulus intensity, or due to differences between experimental in vitro and in vivo models.…”
Section: Discussionmentioning
confidence: 95%
“…Similar as described for traumatic CNS injuries, a strong relationship between PPAR tissue expression and I/R injury could be demonstrated. In kidney I/R, PPAR γ expression was strongly increased in endothelial cells, interstitial cells, and collecting ducts of the kidney peaking from 1.5 to 5 hours after reperfusion [ 64 , 65 ]. Similar upregulation of PPAR γ was detected in the cortical peri-infarct area after focal cerebral ischemia in rats [ 66 ].…”
Section: Ppars In Ischemia/reperfusion Injurymentioning
confidence: 99%